Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 97625 by mathmax by abdo last updated on 08/Jun/20

solve x^2  y^(′′) −(x+1)y^′   =x^2 sinx

solvex2y(x+1)y=x2sinx

Answered by mathmax by abdo last updated on 09/Jun/20

let y^′  =z  so  (e)⇒x^2  z^′ −(x+1)z =x^2  sinx  (he)→x^2 z^′ −(x+1)z =0 ⇒x^2 z^′  =(x+1)z ⇒(z^′ /z) =((x+1)/x^2 ) =(1/x) +(1/x^2 ) ⇒  ln∣z∣ =ln∣x∣−(1/x) +c ⇒z =k∣x∣e^(−(1/x))   let find solution on ]0,+∞[ ⇒  z =kxe^(−(1/x))    mvc method →z^′  =k^′  x e^(−(1/x))  +k(e^(−(1/x))  +x×(1/x^2 )e^(−(1/x)) )  =k^′  x e^(−(1/x))  +k e^(−(1/x))  +(k/x) e^(−(1/x))   (e)⇒k^′  x^3  e^(−(1/x))  +kx^2  e^(−(1/x))  +kx e^(−(1/x))  −kx(x+1)e^(−(1/x))  =x^2  sinx ⇒  (k^′  x^3  +kx^2 +k−kx^2 −kx)e^(−(1/x))  =x^2 sinx ⇒k^′  x^3  e^(−(1/x))  =x^2  sinx ⇒  k^′  =((sinx)/x) e^(1/x)  ⇒ k(x) = ∫^x  ((sint)/t) e^(1/t)  dt +c ⇒  z(x) =x e^(−(1/x)) { ∫^x  ((sint)/t)e^(1/t)  dt +c} =x e^(−(1/x))  ∫^x  ((sint)/t)e^(1/t)  dt +cx e^(−(1/x))    y^′  =z ⇒y(x) =∫^x z(u)du +λ  =∫^x {u e^(−(1/u))  ∫^u  ((sint)/t)e^(1/t)  dt +cu e^(−(1/u)) }du +λ

lety=zso(e)x2z(x+1)z=x2sinx(he)x2z(x+1)z=0x2z=(x+1)zzz=x+1x2=1x+1x2lnz=lnx1x+cz=kxe1xletfindsolutionon]0,+[z=kxe1xmvcmethodz=kxe1x+k(e1x+x×1x2e1x)=kxe1x+ke1x+kxe1x(e)kx3e1x+kx2e1x+kxe1xkx(x+1)e1x=x2sinx(kx3+kx2+kkx2kx)e1x=x2sinxkx3e1x=x2sinxk=sinxxe1xk(x)=xsintte1tdt+cz(x)=xe1x{xsintte1tdt+c}=xe1xxsintte1tdt+cxe1xy=zy(x)=xz(u)du+λ=x{ue1uusintte1tdt+cue1u}du+λ

Terms of Service

Privacy Policy

Contact: info@tinkutara.com